The Conductivity Measure for the Anderson Model - Klein, A.; Müller, P. (Журнал математической физики, анализа, геометрии, 2008)
We study the ac-conductivity in linear response theory for the Anderson tight-binding model. We de ne the electrical ac-conductivity and calculate the linear-response current at zero temperature for arbitrary Fermi energy. In particular, the Fermi energy may lie in a spectral region where extended states are believed to exist.